2008
DOI: 10.1246/cl.2009.64
|View full text |Cite
|
Sign up to set email alerts
|

Design of Alkyl Sulfate Ionic Liquids for Lubricants

Abstract: Tribological properties of alkyl sulfate ionic liquids have been evaluated; hydrophobicity of ionic liquids significantly influenced the tribological characteristics and combination of phosphonium cation with hydrophobic octafluoropentyl sulfate anion afforded good ionic liquid that showed excellent tribological performance.Ionic liquids (ILs) are a new class of fluids and interest has been growing in their application in diverse fields of science and technology.1,2 The tribological properties of ionic liquids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…[47] In addition, phosphonium cation-based ILs with appropriate anions show excellent tribological properties more than imidazolium-based ILs. [50][51][52] As expected, adsorption species contained phosphoric compound. Also a new IL was synthesized by combining imidazolium cation and phosphate anion.…”
Section: Tailored Lubricantssupporting
confidence: 79%
“…[47] In addition, phosphonium cation-based ILs with appropriate anions show excellent tribological properties more than imidazolium-based ILs. [50][51][52] As expected, adsorption species contained phosphoric compound. Also a new IL was synthesized by combining imidazolium cation and phosphate anion.…”
Section: Tailored Lubricantssupporting
confidence: 79%
“…So it can be concluded that the lubricant with phosphonate anion is suitable for the steel-aluminium contact than that with the hexafluorophosphate anion. As is known that anion plays an important role in the tribological performance of ionic liquids [23,24]. It can not only make the viscosity change but also have an impact on the formation of boundary lubricating film (adsorption and chemical reaction film) [9].…”
Section: Constant Load and Frequency Experimentsmentioning
confidence: 99%
“…From the practical point of view, RTILs can boast a wide variety of potential applications 7,8 , not limited to components of robust electrolytes for electrochemical devices 10,11 , reaction medias 12 , lubricants 13 , solvents for synthetic and catalytic schemes 14,15 . The prominent properties of RTILs, as salts with very low melting points, are determined by the structure and inter-ionic interactions.…”
Section: Introductionmentioning
confidence: 99%